2019
DOI: 10.3390/ijerph16245085
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Unsafe Sexual Behavior among Factory Workers in the Context of Rapid Industrialization in Northern Vietnam

Abstract: Industrial workers or factory workers, especially migrant workers, have been found to be vulnerable populations at risk of sexually transmitted infections (STIs). However, there has been a gap in literature regarding health behaviors of migrant factory workers. We conducted a cross-sectional study among 230 factory workers in Hanoi and Bac Ninh cities in Northern Vietnam from July to September 2018 to identify sexual risk practices and related factors among migrant and nonmigrant factory workers. Information c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 40 publications
4
22
2
Order By: Relevance
“…Main findings are presented in Table 1. The result showed that underlying health problems were common among industrial workers (Pham et al, 2019;Tran et al, 2019b;Tran et al, 2019c), with many suffering occupational diseases (Quynh Nguyen et al, 2017;Tran et al, 2016) and/or work-related injuries (Marucci-Wellman et al, 2010;Phung et al, 2008;Ratnasingam et al, 2012). A high prevalence of respiratory system problems was also reported (Chien et al, 2002).…”
Section: Resultsmentioning
confidence: 95%
“…Main findings are presented in Table 1. The result showed that underlying health problems were common among industrial workers (Pham et al, 2019;Tran et al, 2019b;Tran et al, 2019c), with many suffering occupational diseases (Quynh Nguyen et al, 2017;Tran et al, 2016) and/or work-related injuries (Marucci-Wellman et al, 2010;Phung et al, 2008;Ratnasingam et al, 2012). A high prevalence of respiratory system problems was also reported (Chien et al, 2002).…”
Section: Resultsmentioning
confidence: 95%
“…T he vulnerability to Human Immunodeficiency Virus (HIV) and sexually transmitted infections (STIs) have been reportedly high among industrial workers, especially the migrants. [1][2][3][4] The widespread of HIV and STI has also been described as the most important determinant of the burden of HIV in Sub-Saharan Africa. 5,6 Some factors associated with unsafe behavioural changes such as unsafe sexual activities, excessive drinking, migration, mobility, and separation from family.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Some factors associated with unsafe behavioural changes such as unsafe sexual activities, excessive drinking, migration, mobility, and separation from family. 1,7 The risk of heterosexual HIV transmission is greater among workers in rural communities due to their lack of access to HIV treatment and prevention or inadequate facilities, exposure to sex workers and work situations. 1 In sub-Saharan Africa, particularly the rural communities, the definition of sexual activities is determined by cultural belief, social and economic context.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations